Heat-insulating ceramics which have a nanoporous structure and are made with the use of ash-bearing wastes from power plants; Refractories and Industrial Ceramics; Vol. 55, iss. 6 - Vakalova T. V. Tatjana Viktorovna; Khabas (Habas) T. A. Tamara Andreevna; Revva I. B. Inna Borisovna; Pavlova I. A. Irina Anatoljevna (Raw materials, 2015)
Title screen